2017
DOI: 10.1167/iovs.16-20712
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Alpha (TNF-α) Disrupts Kir4.1 Channel Expression Resulting in Müller Cell Dysfunction in the Retina

Abstract: Our findings demonstrate that Kir4.1 channels possess a diurnal rhythm, and this rhythm is dampened with diabetes, thereby suggesting that the increase in TNF-α is detrimental to normal Kir4.1 rhythm and expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…The gliosis of Müller cells is associated with a functional uncoupling from neurons, which contributes to neurodegeneration and impedes tissue repair and regular neuroregeneration. Gliotic Müller cells have direct cytotoxic effects mediated by the release of soluble proinflammatory cytokines including TNFα ( Hassan et al, 2017 ), IL-1β ( Yego et al, 2009 ), ICAM-1 ( Wang et al, 2010 ), and MCP-1 ( Eastlake et al, 2016 ). In primary cultured retinal Müller cells, LPS (1000 ng/ml) stimulation significantly upregulated the expression of GFAP, TNFα, IL-1β, ICAM-1, and MCP-1 and downregulated the functional protein AQP4.…”
Section: Discussionmentioning
confidence: 99%
“…The gliosis of Müller cells is associated with a functional uncoupling from neurons, which contributes to neurodegeneration and impedes tissue repair and regular neuroregeneration. Gliotic Müller cells have direct cytotoxic effects mediated by the release of soluble proinflammatory cytokines including TNFα ( Hassan et al, 2017 ), IL-1β ( Yego et al, 2009 ), ICAM-1 ( Wang et al, 2010 ), and MCP-1 ( Eastlake et al, 2016 ). In primary cultured retinal Müller cells, LPS (1000 ng/ml) stimulation significantly upregulated the expression of GFAP, TNFα, IL-1β, ICAM-1, and MCP-1 and downregulated the functional protein AQP4.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, several authors have also reported strong negative correlations between the extent of membrane lipid peroxidation and NKA activity in vivo in illnesses as diverse as cardiovascular disease, SZ, and BPD [255,256,261]. The relationship between increased membrane lipid peroxidation and increasing NKA dysfunction appears to be mediated by decreased membrane fluidity and PUFA content [260,262]. This is of importance as several studies have reported a significant increase in NKA activity following dietary supplementation with PUFAs [260,[263][264][265].…”
Section: Nutritional Ketosis Astrogliosis and Nka Functionmentioning
confidence: 97%
“…The causative role played by oxidative and nitrosative stress in NKA downregulation is further emphasized by studies reporting that prolonged use of antioxidant combinations such as vitamin C and E or N-acetylcysteine, α-tocopherol, and α-lipoic acid can produce clinically significant increases in NKA activity in the brain and periphery [259,260]. Thus, there is a prospect that the welldocumented antioxidant properties of the KD may exert a similar effect assuming a similar effect size and may well underpin the observations reporting a positive effect of the KD on improving NKA function discussed above.…”
Section: Nutritional Ketosis Astrogliosis and Nka Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the polarized pattern of Kir4.1 exhibits a strong decrease in perivascular regions in diabetic retinas expressing Müller cell markers [ 11 , 12 ]. Our studies demonstrate that Müller cells exhibit a functional clock with a diurnal rhythm of Kir4.1 and diabetes disturbs the natural circadian rhythm of Kir4.1 [ 13 ]. AGEs are known to induce Müller cell dysfunction [ 14 ], but it remains unknown how AGE-modification of BM affects Kir4.1 channels in diabetes.…”
Section: Introductionmentioning
confidence: 99%